The association of GSTT1 deletion polymorphism with lung cancer risk among Chinese population: evidence based on a cumulative meta-analysis - Wang Y (OncoTargets and Therapy, 2015)
Yadong Wang,1 Haiyan Yang,2 Haiyu Wang11Department of Toxicology, Henan Center for Disease Control and Prevention, Zhengzhou, People’s Republic of China; 2Department of Epidemiology, School of Public Health, Zhengzhou University, Zhengzhou, People’s Republic of ChinaObjective: Previous studies investigating the relationship between glutathione S-transferase T1 (GSTT1) gene deletion polymorphism and lung cancer risk among Chinese population produced inconsistent results. To obtain a precise conclusion, we performed this meta-analysis to evaluate the association between GSTT1 deletion polymorphism and lung cancer risk among Chinese population.Methods: The databases of Medline/PubMed, Embase, Web of Science, Wanfang Med Online, and Chinese National Knowledge Infrastructure were searched. The strength of the association was assessed by odds ratio (OR) with 95% confidence intervals (95% CI).Results: Overall, we found an increased lung cancer risk among subjects carrying GSTT1 null genotype compared with those carrying present genotype (OR =1.31, 95% CI: 1.12–1.52) on the basis of 20 studies with 3,351 cases and 4,683 controls. We also observed an increased risk of lung cancer among subjects carrying GSTT1 null genotype compared with those carrying present genotype in stratified analyses (OR =1.31, 95% CI: 1.11–1.55 for healthy subjects-based control; OR =2.29, 95% CI: 1.84–2.85 for squamous cell carcinoma and OR =1.47, 95% CI: 1.22–1.77 for adenocarcinoma, respectively).Conclusion: This meta-analysis suggested that GSTT1 deletion polymorphism might contribute to lung cancer risk among Chinese population.Keywords: lung cancer, risk, GSTT1, polymorphism, meta-analysis, Chinese